Lipase-catalyzed preparation of mono- and diesters of ferulic acid - Sandoval, Georgina; Quintana, Paula Gabriela; Baldessari, Alicia; Ballesteros, Antonio O.; Plou, Francisco J. (Biocatalysis and Biotransformation)
Lipophilic and stable derivatives of ferulic acid are required to improve its effi cacy in fatty foods and to optimize its use in cosmetic and pharmaceutical preparations. We report an improved synthesis of ferulic acid monoesters (ethyl ferulate and lauryl ferulate) using immobilized lipase from Candida antarctica B (CALB) in diisopropyl ether (DIPE). Maximum yields were 89% and 85% in 200 h for ethyl and lauryl ferulate, respectively. Ethyl ferulate was further acylated with vinyl esters to form ferulate diesters. 4-Acetoxy-ethyl ferulate was obtained with the immobilized lipase from Alcaligenes sp. (QLG) with 59% yield in 72 h, whereas 4-dodecanoyloxy-ethyl ferulate (a new compound) was synthesized with 52% yield in 72 h using CALB. DIPE was the best solvent for the transesterifi cations. Finally, the anti-infl ammatory activity of the synthesized derivatives was evaluated in vitro; the compounds bearing a dodecyl chain showed improved anti-infl ammatory activity compared with short-chain esters. Fil: Sandoval, Georgina. Consejo Superior de Investigaciones Científicas. Instituto de Catalisis y Petroleoquímica; España Fil: Quintana, Paula Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina Fil: Baldessari, Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina Fil: Ballesteros, Antonio O. Consejo Superior de Investigaciones Científicas. Instituto de Catalisis y Petroleoquímica; España Fil: Plou, Francisco J. Consejo Superior de Investigaciones ...